Evaluating the impact of canal restoration in Kotagala, Nuwara Eliya District, Sri Lanka - Herath, H. M. M.; Alahacoon, Niranga; Sivananthan, Piriyanka; Attoh, Emmanuel M. N. A. N.; Amarnath, Giriraj (International Water Management Institute, 2024)
The impact evaluation of the canal restoration project in Kotagala, Nuwara Eliya District, Sri Lanka, highlights the significant benefits of locally led adaptation measures in addressing climate risks, particularly flooding. The restoration, completed in 2023 by International Water Management Institute supported through the CGIAR initiatives on Climate Resilience “ClimBeR” ACTION grant and supported by Japan’s Ministry of Agriculture, Forestry and Fisheries, focused on rehabilitating a 2 km stretch of the canal running through the. Chrystler's Farm The initiative aimed to improve water flow, reduce flood risks, and enhance the resilience of the local community, which had faced recurring floods due to heavy rainfall, sedimentation, and waste mismanagement.